Atresia of the esophagus - thoracotomy vs thoracoscopy - Robert Chudzik; Katarzyna Jarosz-Chudzik; Maria Gołębiowska; Marcin Kulczyński; Małgorzata Pucułek (Kazimierz Wielki University, 2018)
Esophageal atresia is a congenital medical condition associated with the disorder of the alimentary tract. It is usually associated with one or more fistulas to the trachea. Esophageal atresia is often associated with other congenital defects. The most frequent anomalies with atresia of the esophagus are those that occur in the VACTERL association. The incidence of oesophageal atresia mention in the literature varies 0.7-4.55/10000, because of the different percentage of defects other than esophageal atresia and associated with esophageal atresia changes. The etiology of esophageal atresia is mainly unknown, but it is considered multifactorial, including genetic and environmental factors. Indeed, 6-10% of cases of esophageal atresia have been diagnosed with a chromosomal abnormality or syndrome. For the purpose of this study, we analyzed the current papers on esophageal atresia found in the PubMed database. Traditionally, the esophageal atresia has been operated by the right posterior thoracotomy. The first thoracoscopic repair of classic esophageal atresia was performed in 1999, and the first successful thoracoscopy of the tracheo-oesophageal fistula a year later. Together with these milestones, numerous health centers have begun adapting this surgical technique. Although thoracoscopic surgery in the case of esophageal atresia in patients with tracheo-bronchial fistula was conducted in many highly developed children's surgery centers, the safety and efficacy of this method remained controversial. The benefits of thoracoscopic surgery are obvious, including excellent visualization, less use of post-operative drugs and cosmetic effects. Jaureguiza et al. described the "scaly scapula", chest wall deformity, scoliosis and the development of the bad nipple in patients who underwent open surgery due to esophageal atresia with the accompanying tacha-oesophageal fistula. In the case of open thoracotomy, it was necessary to withdraw the lungs to expose the posterior mediastinum, resulting in lung damage and respiratory complications. Compared to the open surgery, thoracoscopy significantly reduced the time of hospital stay and the moment of the first oral meal. However, thoracoscopy was associated with a longer time of surgery. The incidence of leaks, narrowings, pulmonary complications, and blood loss were similar in both surgical technique. It seems that the benefits of thoracoscopy are significant.